"Saturday night fever": ecstasy related problems in a London accident and emergency department. Issue 5 (September 1998) - Williams, H; Dratcu, L; Taylor, R; Roberts, M; Oyefeso, A
Abstract : OBJECTIVES: To report on the extent and nature of acute MDMA (ecstasy) related problems presenting to a large London hospital's accident and emergency (A&E) department. METHOD: The computerised attendance records for all patients attending the A&E department over a 15 month period were retrospectively screened. Potential cases thus identified had their case notes systematically reviewed to confirm the history of MDMA use and to extract other relevant data. RESULTS: Forty eight consecutive MDMA related cases were identified. All were in the 15-30 year age group with the majority presenting in the early hours at weekends and having consumed the drug at a night club. The mean number of tablets consumed was two and almost 40% had taken MDMA before. Polydrug use was common with half of the sample having concurrently taken another illicit substance–most commonly other stimulants (amphetamines and cocaine). A wide range of adverse clinical features was found. The most common symptoms were vague and non-specific such as feeling strange or unwell, however many patients had collapsed or lost consciousness. The most common signs elicited were related to sympathetic overactivity, agitation/disturbed behaviour, and increased temperature. The more serious complications of delirium, seizures, and profound unconsciousness (coma) were commoner when MDMA was used in combination with other substances. CONCLUSIONS: For young adults presenting late at night at weekends and exhibiting symptoms of sympathetic overactivity, disturbed behaviour, and increased temperature ("Saturday night fever") the use of stimulant dance drugs especially MDMA should be suspected. As MDMA use does not appear to occur in isolation, the clinical picture is likely to be complicated by multiple rather than single drug ingestion. This poses increased diagnostic and management challenges for A&E staff who typically represent the front line response to dance drug related problems.